Meta‐analysis of α‐blockade versus no blockade before adrenalectomy for phaeochromocytoma. Issue 2 (5th January 2020) - Schimmack, S.; Kaiser, J.; Probst, P.; Kalkum, E.; Diener, M. K.; Strobel, O.
Abstract : Background: Preoperative α‐blockade in phaeochromocytoma surgery is recommended by all guidelines to prevent intraoperative cardiocirculatory events. The aim of this meta‐analysis was to assess the benefit of such preoperative treatment compared with no treatment before adrenalectomy for phaeochromocytoma. Methods: A systematic literature search was undertaken in MEDLINE, Web of Science and CENTRAL without language restrictions. Randomized and non‐randomized comparative studies investigating preoperative α‐blockade in phaeochromocytoma surgery were included. Data on perioperative safety, effectiveness and outcomes were extracted. Pooled results were calculated as an odds ratio or mean difference with 95 per cent confidence interval. Results: A total of four retrospective comparative studies were included investigating 603 patients undergoing phaeochromocytoma surgery. Mortality, cardiovascular complications, mean maximal intraoperative systolic and diastolic BP, and mean maximal intraoperative heart rate did not differ between patients with or without α‐blockade. The certainty of the evidence was very low owing to the inferior quality of studies. Conclusion: This meta‐analysis has shown a lack of evidence for preoperative α‐blockade in surgery for phaeochromocytoma. RCTs are needed to evaluate whether preoperative α‐blockade can be abandoned. Abstract : Preoperative α‐blockade in phaeochromocytoma surgery is recommended by all guidelines to prevent intraoperative cardiocirculatory events. In this meta‐analysis, a total of four retrospective comparative studies were included investigating 603 patients undergoing phaeochromocytoma surgery. Mortality, cardiovascular complications, mean maximal intraoperative systolic and diastolic BP, and mean maximal intraoperative heart rate (HR) did not differ between patients with or without α‐blockade. Time for an RCT? A video abstract is available at https://youtu.be/Mq1dX6x_oFU Abstract : Antecedentes: Todas las guías recomiendan el bloqueo alfa preoperatorio en la cirugía del feocromocitoma para prevenir eventos cardiocirculatorios intraoperatorios. El objetivo de este metaanálisis fue evaluar el beneficio de dicho tratamiento preoperatorio antes de la adrenalectomía por feocromocitoma en comparación con ningún tratamiento. Métodos: Se realizó una búsqueda sistemática de la literatura en MEDLINE, Web of Science y CENTRAL sin restricciones de idioma. Se incluyeron estudios comparativos aleatorizados y no aleatorizados que investigaron el bloqueo alfa preoperatorio en la cirugía del feocromocitoma. Se extrajeron los datos en relación a la seguridad perioperatoria, la efectividad y los resultados. Los resultados agrupados se mostraron como razón de oportunidades (odds ratio, OR) o diferencia de medias (MD) con el correspondiente i.c. del 95%. Resultados: Se incluyeron un total de cuatro estudios comparativos retrospectivos que analizaron a 603 pacientes sometidos a cirugía del feocromocitoma. La mortalidad, las complicaciones cardiovasculares, la media del valor máximo de la presión arterial sistólica y diastólica intraoperatoria y la media del valor máximo de la frecuencia cardíaca intraoperatoria no difirieron entre pacientes con o sin bloqueo. La certeza de la evidencia fue muy baja debido a la baja calidad de los estudios. Conclusión: Este metaanálisis demuestra la falta de evidencia del bloqueo alfa preoperatorio en la cirugía del feocromocitoma. Se necesitan ensayos controlados aleatorizados para evaluar si se puede abandonar el bloqueo alfa preoperatorio.